Team related factors influencing project performance as perceived by project managers in Malaysia - Fung, Han Ping (2014)
As more and more project teams are formed to help Malaysian organizations to achieve their objectives that individual efforts alone cannot achieve, studies showed that returns of project investment is not very encouraging as people issue is a major contributor. Since a typical project requires a team of members and project manager to deliver its objectives, there is compelling reason to understand what are the team related factors influencing project performance. This research developed a model underpinned on Cohen and Bailey's (1997) Team Effectiveness Framework as well as General Systems Theory (Bertalanffy, 1968; McGrath, 1984) to empirically analyze some of the critical factors that can influence project performance. Data were collected through an online survey from members of the Project Management Institute Malaysia Chapter in which sample of 201 respondents were randomly selected. The model and data were then tested using Partial Least Squares whereby the results showed that a project manager's leadership roles, team building & participation and team shared mental models are important but not directly influencing project performance. These three factors are influencing project performance indirectly through interaction among themselves as well as through team attitudinal outcomes which include team trust and team satisfaction. These three factors also can influence team behavioral outcomes directly but team behavioral outcomes which include team cohesion and team effectiveness alone do not directly influencing project performance.